Descarbonização corporativa e conformidade regulatória: um estudo comparativo das práticas de reporte de GEE da AB InBev e da Unilever frente às exigências legais brasileiras e europeias - Almeida, Julio Cesar de Oliveira (Universidade Federal de São Carlos, 2026)
The intensification of climate change and the consequent tightening of national and international regulatory frameworks have placed the management and reporting of Greenhouse Gases (GHG) as strategic imperatives for the industrial and corporate sectors. This study analyzes the regulatory and methodological panorama of atmospheric emissions at state, federal, and international levels, evaluating GHG management and reporting practices from the perspective of corporate sustainability in multinationals. The research, qualitative-descriptive in nature, is based on documentary and bibliographical research, articulating primary normative sources CONAMA Resolution No. 506/2024, State Decree No. 60.076/2025 (PMEA-CETESB), and Directive (EU) 2015/2193 (MCPD), international inventory methodologies, GHG Protocol and ISO 14064-1—, and the 2025 annual sustainability reports of the multinationals Anheuser-Busch InBev (AB InBev) and Unilever PLC. The comparative analysis of the three jurisdictions shows convergences in the common objective of controlling local pollutants (Particulate Matter, $\text{SO}_2$, and $\text{NO}_x$) and relevant divergences in compliance deadlines, the stringency of technical emission limits, and regulatory philosophy—oscillating between the static enforcement paradigm predominant in the Brazilian federal sphere and the progressive continuous improvement approach adopted by both PMEA-CETESB and European regulation. At the corporate level, data verified by independent auditing demonstrate that AB InBev surpassed its emissions intensity target with a 31.9% reduction in Scopes 1, 2, and 3 against the 2017 baseline, while Unilever advances toward its operational neutrality target (Scopes 1 and 2) by 2030, with a 77% reduction already accumulated relative to the 2015 baseline. Both corporations adopt the European Sustainability Reporting Standards (ESRS) as a transparency standard, signaling convergence between regulatory requirements and market practices. The study concludes that regulatory compliance alone is a necessary but not sufficient condition for the systemic decarbonization required by the commitments of the Paris Agreement and COP28, making the integration between local pollutant monitoring, corporate GHG inventories, and circular economy-oriented avoided emissions strategies indispensable.
Corporate decarbonization and regulatory compliance: a comparative study of the GHG reporting practices of AB InBev and Unilever in relation to Brazilian and European legal requirements
Keywords: Emissões Atmosféricas; Gases de Efeito Estufa; GHG; Sustentabilidade Corporativa; Sustentabilidade Corporativa; CIENCIAS EXATAS E DA TERRA::QUIMICA; 9. Indústria, Inovação e Infraestrutura; 13. Ação contra a Mudança Global do Clima